Role of Forest Resources to Local Livelihoods: The Case of East Mau Forest Ecosystem, Kenya - D. K. Langat; E. K. Maranga; A. A. Aboud; J. K. Cheboiwo (International Journal of Forestry Research)
Forests in Kenya are threatened by unsustainable uses and conversion to alternative land uses. In spite of the consequences of forest degradation and biodiversity loss and reliance of communities on forests livelihoods, there is little empirical data on the role of forest resources in livelihoods of the local communities. Socioeconomic, demographic, and forest use data were obtained by interviewing 367 households. Forest product market survey was undertaken to determine prices of various forest products for valuation of forest use. Forest income was significant to households contributing 33% of total household income. Fuel wood contributed 50%, food (27%), construction material (18%), and fodder, and thatching material 5% to household forest income. Absolute forest income and relative forest income (%) were not significantly different across study locations and between ethnic groups. However, absolute forest income and relative forest income (%) were significantly different among wealth classes. Poor households were more dependent on forests resources. However, in absolute terms, the rich households derived higher forest income. These results provide valuable information on the role of forest resources to livelihoods and could be applied in developing forest conservation policies for enhanced ecosystem services and livelihoods.